Modelling Non-Renewable Energy in Mauritius: In Quest for Sustainable Policies towards a Greener Economy - Ramlall, Indranarain (International Journal of Energy Economics and Policy, 2012)
This paper sheds light on the interaction between energy consumption and energy production in an upper-income developing country. Results show that Industrial consumption of energy in Mauritius is driven mainly by Fuel source while Commercial use is accommodated by a mixture of Coal and Fuel sources. Bagasse and Hydro energy generations undermine the use of Coal and Fuel, all demonstrating an inherent greening phenomenon embedded in the energy process. However, their size effects are low. Findings further confirm sustainability in energy generation and absorption based on a slightly above one long-term elasticity coefficient between energy production and consumption. Overall, results suggest that Mauritius has to implement vigorous measures in view of greening its energy processes. Policy wise, this could signify the urgent need of both Commercial and Industrial usage taxes to stimulate a greener economy. Keywords: VAR; Mauritius; Sustainable/Green Policies; Variance Decomposition; Impulse Response; Energy Policies JEL Classifications: Q4